Worsening of Retinal Detachment after Cataract Surgery in the Eye with Persistent Fetal Vasculature - Yuri Aikawa; Takayuki Baba; Tomohiro Nizawa; Hirotaka Yokouchi; Shuichi Yamamoto (Case Reports in Medicine)
Purpose. To report a case of persistent fetal vasculature (PFV) with a retinal detachment that worsened after cataract surgery. Pars plana vitrectomy (PPV) was performed which reduced the vitreous traction and reattached the retina. Observations. A 20-year-old Myanmarese woman presented with a mature cataract, and her vision was light perception. She underwent uneventful cataract surgery with implantation of an intraocular lens. Her visual acuity improved to 20/200 immediately after the surgery. However, fibrotic tissue was observed between the optic nerve head and the posterior capsule. She was diagnosed with PFV, and she was followed without any intervention. One and a half years after the cataract surgery, she had an advanced retinal detachment which extended over the inferior two quadrants. Her vision deteriorated to 20/400. She underwent PPV, and the PFV tissue was removed which resulted in the reattachment of the retina. The visual acuity improved to 20/60. Conclusions. Surgeons should be aware that it is possible to worsen a retinal detachment after cataract surgery in the eyes with PFV. A simple technique to release the anterior-posterior traction by the PPV was sufficient to achieve the reattachment of the retina.